ALİFATİK DİAMİNLERDEN ELDE EDİLEN SCHİFF BAZI KOMPLEKSLERİNİN SENTEZİ VE KARAKTERİZASYONU - AKPOLAT, ŞAZİME SEVİNAY (Fırat Üniveristesi, 2008)
Bu çalışmada, 2-{(2-[(2-Hidroksifenil)amino]etil)imino}fenol ligandı (LH2) ve bu ligandın, Co(II), Ni(II), Cu(II), Zn(II) kompleksleri hazırlandı.Etilendiamin ve Salisilaldehitin kondenzasyonu ile 2-{(2-[(2-Hidroksifenil)-amino]etil)imino}fenol ligandı (LH2) hazırlandı. Bu ligandın kompleksleri Co(NO3)2.6H2O, Ni(NO3)2.6H2O, Cu(NO3)2.3H2O ve Zn(NO3)2.6H2O tuzları ile hazırlandı.2-{(2-[(2-Hidroksifenil)amino]etil)imino}fenol ligandının (LH2) kompleksleri [Co2(LH)2(NO3)2].1.5.H2O, [NiL], [Cu2(LH2)2(NO3)2].2NO3 ve [Zn2(LH2)2-(NO3)4(H2O)2] yapılarındadırlar.Ligandın ve komplekslerin yapıları IR, Elementel Analiz, Magnetik Süsseptibilite, UV-VIS, 1H-NMR, TGA, DTA spektroskopisi teknikleri kullanılarak tespit edildi.

In this work, 2-{(2-[(2-Hydroxyphenyl)amino]ethyl)imino} ligand (LH2) and its Co(II), Ni(II), Cu(II), Zn(II) complexes were synthesized.2-{(2-[(2-Hydroxyphenyl)amino]ethyl)imino} ligand (LH2) has been prepared via the condensation of ethylenediamine and salicylaldehyde. The complexes of this ligand were prepared with Co(NO3)2.6H2O, Ni(NO3)2.6H2O, Cu(NO3)2.3H2O, Zn(NO3)2.6H2O salts.The structure of the metal complexes of (LH2) are [Co2(LH)2(NO3)2].1.5.H2O, [NiL], [Cu2(LH2)2(NO3)2].2(NO3), [Zn2(LH2)2(NO3)4 (H2O)2].The structures of ligand and metal complexes were determined by using IR, Elemental Analysis, Magnetic Susceptibility, UV-VIS, 1H-NMR, TGA, DTA, spectroscopic tecniques
Synthesis and characterization of schiff base complexes from alifatic diamine
Keywords: Kimya